Exploring women’s experiences participating in yoga after a cancer diagnosis: a protocol for a meta-synthesis - Jenson Price; Jennifer Brunet (Systematic Reviews, 2022)
Abstract Background The benefits of yoga for clinical and non-clinical populations have been summarized in published systematic reviews. The vast majority of systematic reviews on the topic are syntheses of quantitative research that evaluated the effects of yoga. As qualitative research related to women’s experiences participating in yoga after a cancer diagnosis is growing in quantity, systematic synthesis and integration of qualitative research are necessary to facilitate the transfer of knowledge. This paper describes the protocol for a meta-synthesis of qualitative research exploring women’s experiences participating in yoga after a cancer diagnosis. Methods Using a meta-study methodology, six electronic databases were searched to identify relevant articles. Additionally, the reference lists of relevant articles retrieved during the electronic database search were scanned to identify other relevant articles. Two reviewers independently screened the titles and abstracts, retaining those that appeared to relate to the review objectives. Next, they reviewed the retained full-text articles to assess eligibility according to four inclusion criteria. They will extract data from eligible studies and assess the quality of included studies. Data analysis will involve three main analytical steps: meta-data analysis, meta-method analysis, and meta-theory analysis. Findings from the three analytical steps will be interpreted collectively to generate additional insights beyond the findings of the primary studies to facilitate a more comprehensive understanding of women’s experiences participating in yoga after a cancer diagnosis. Discussion By systematically collecting, analysing, and interpreting findings across multiple primary qualitative studies, we will develop an overarching narrative and interpretation of the role and value of yoga for women diagnosed with cancer. A synthesis of qualitative research is vital as it embraces the heterogeneity of the research so as to provide important context for understanding the experiences of various women participating in yoga. Systematic review registration PROSPERO CRD42021229253